Sources of Inefficiency in a Representative Democracy: A Dynamic Analysis - Besley, Timothy; Coate, Stephen (American Economic Review, 1998)
This paper studies the efficiency of policy choice in representative democracies. It extends the citizen-candidate model of democratic policy-making to a dynamic environment. Equilibrium policy choices are shown to be efficient in the sense that in each period, conditional on future policies being selected through the democratic process, there exists no alternative current policy choices which can raise the expected utilities of all citizens. However, policies that would be declared efficient by standard economic criteria are not necessarily adopted in political equilibrium. The paper argues that these divergencies are legitimately viewed as "political failures."